Youth Reports of Parental Strategies and Sense of Coherence: Are Experiences of Being Victim of Physical Abuse Reflected?. (November 2019) - Thulin, Johanna; Nilsson, Doris; Kjellgren, Cecilia
This article explores adolescent's reports of parental strategies and sense of coherence (SOC). Building on the suggested impact of child physical abuse, this study compares reports from a group of physically abused youth and a group of non-abused youth. Independent t -test, correlations and hierarchical linear regression analysis were computed. Findings indicate that parents' use of corporal punishment could affect how youth report their parent's parental strategies. Physically abused youth report less parental involvement and positive parenting as well as more inconsistent parenting than non-abused youth. Furthermore, physically abused youth report a significant lower SOC than non-abused youth. Being a victim of physical abuse had a unique contribution on SOC, even after controlling for other parental strategies. Taken together, the results suggest that child physical abuse affects both the youth's inner SOC as well as their reports of parental strategies in several ways. Implications for practice are discussed in this article.